The Effect of Poverty and Open Unemployment Rate on the Human Development Index in West Nusa Tenggara Province - Baehaqi; Dea Triwahyu; Baiq Rizka Milania Ulfah (LP2M IAIN Palopo, 2026)
This research aims to determine the effect of the Poverty Rate and Open Unemployment Rate (OUR) on the Human Development Index (HDI) in the NTB Province from 2010 to 2024. The research method used is a quantitative method with a causal approach (causality). The data analysis technique uses a multiple linear regression model with the help of SPSS software, accompanied by classical assumption tests and hypothesis tests. This study uses secondary data in the form of time series data with a period of 15 years, from 2010 to 2024. Data were obtained from official government agencies, specifically the Central Statistics Agency (BPS) of NTB Province. The research results show that partially, the Poverty Rate and the Open Unemployment Rate have a negative and significant impact on the HDI in the NTB Province. Simultaneously or together, these two variables also have a significant impact on the HDI in the NTB Province. To improve the welfare and quality of human development in a region, local governments must prioritize policies and programs that can reduce poverty and unemployment rates in order to encourage the increase of HDI in NTB Province.